Drug Menace in India: A status report of law and loopholes in the implementation - Dr. , KVK Santhy (International Journal of Psychosocial Rehabilitation, 2016)
India is recognized as one of the leading global players in the manufacture of pharmaceuticals as it is fourth in terms of volume and thirteenth in terms of value of production. It is also recognized that the cost of drugs produced in India is amongst the lowest in the world. It is estimated that industry has the potential to achieve Rs 1,000,000 million in formulations with bulk drug production going up from Rs 80000 million to Rs 250,000 million by the year 2010. The pharmaceuticals sector has witnessed tremendous growth over the past few years – from a turnover of Rs 50000 million in 1990 to over Rs 500,000 million during 2004-2005. Exports also grew very significantly during this period to over Rs 167000 million. Indian exports supply more than 200 countries around the globe including the highly regulated markets of US, Europe, Japan and Australia. The value of exports of drugs and pharmaceuticals increased to over Rs. 21,000 crore or US 4.7 billion in 2005-06 from around Rs. 78578 million in 2004-05, while their imports has been around 999.97 million US in the year 2005-062. It is estimated that the industry has the potential to achieve over Rs. 1,000,000 million in formulations and bulk drug production by the year 2010.3 This article delineates the concerned law and infra structure in place in this country and how the present system is unable to deal with the counterfeit drug menace properly.